Produção e caracterização mecânica de compósitos de resina poliuretana à base de óleo de mamona e fibras de rami, sisal e bucha vegetal - Sousa, Lauren Karoline de (2013)
In recent years the research on new materials for application in construction had intensified in order to rationalize the manpower in the sector. Thereat, many studies are being conducted with the goal of developing composites for use in construction. The use of composites as wall panels is sustainable when the materials used are biodegradable. The objective of this research is produce and characterize polymeric composites using a castor oil polyurethane matrix reinforced with ramie, sisal and sponge gourd fibers. The composites were reinforced with unidirectional and randomly distributed fibers, with volume of 25%, 35%, 45% and 55%. The composites were produced compressed at room temperature, interleaving fiber and resin to secure the void reduction and adhesion of the fiber to the matrix. Through the tensile test the tensile strength, Young s modulus and maximum deformation were determined. The best results were obtained in composites reinforced with 45% unidirectional continuous sisal fibers. The composites reinforced with ramie fiber also showed excellent Young s modulus (23 GPa). Therefore, the study showed that fiber sisal, rami and sponge gourd reinforced castor oil polyurethane composites presented good properties for many uses in civil construction.